Semantic interoperability with heterogeneous information systems on the internet through automatic tabular document exchange - Yang, Shuo; Guo, Jingzhi; Wei, Ran (Information systems (Oxford), 2017)
Internet is a common information space populated with many entities (e.g., Internet of Things) with different information system types. Each of them has its own context of how to build and process documents (e.g., form documents). This leads to heterogeneous documents in terms of syntax and semantics, which are difficult to make information fusion from one context to another. To resolve this problem, this paper uses semantic interoperability technique which consists of two automatic stages including consistent data understanding and reasonable data usage. To implement semantic interoperability, this paper proposes a novel automatic tabular document exchange (DocEx) framework comprised of a new tabular document model (TabDoc) and a semantic inference scheme to fit the two stages above respectively. In this TabDoc model, a new Tabular Document Language (DocLang) as a communication medium between users and devices is provided, which is not only an information representation language but also a rule language for semantic inference as well. Abstract sub-tree-based semantic relations constructing the logical structure of a tabular document are separated from their presentational structures, clarifying the relationship between semantic groups (e.g., a cell or a block) with the help of a common dictionary CONEX. Besides, this paper proposes a semantic inference algorithm (SIA) executing the inference procedure on received tabular documents created by a Table Designer system which integrates with SIA. Finally, the proposed framework is applied to the processing of flight ticket booking in a realistic e-business scenario. The results show that the proposed method in this paper improves the performance of information fusion among different information systems on the Internet. •Information fusion is realized by consistent interpretation and usage of documents.•The proposed DocLang syntax only defines an element and will not restrict user input.•Automatic document understanding and processing is implemented by a rule language.•TabDoc model contains syntactic and semantic representation for document reusability.•Tabdoc rule syntax is used for semantic extraction in a declarative manner.